Characterization of ACLY Knockdown in Hepatocellular Carcinoma - Wu, Jianhan (My University, 2020)
Lipid is co-opted by cancer cells to meet the metabolic demands of uncontrolled cell proliferation. ATP citrate lyase (ACLY) plays an important role in lipid metabolism by catalyzing the synthesis of acetyl-CoA from mitochondrial citrate thus providing the essential cytosolic precursor for subsequent fatty acid/cholesterol synthesis. Previously, we demonstrated that inhibition of acetyl-CoA carboxylase (ACC) leads to impaired hepatic DNL and reduced incidence of hepatocellular carcinoma (HCC). Given that ACC acts downstream of ACLY, herein, we characterized the role of ACLY as a lipid metabolic regulator of HCC progression. Sourcing from publicly available patient transcriptome datasets, we found that ACLY expression positively correlates with HCC progression and mortality. Inducible knockdown of ACLY expression in Hep3B and SK-Hep1 cells reprograms lipid metabolism through reducing glucose mediated de novo lipogenesis (DNL), inducing fatty acid oxidation and upregulating acetate mediated DNL via the acyl-CoA synthetase 2 (ACSS2) pathway. This is accompanied by decreased cell proliferation, colony formation and invasion. In vivo, orthotopic modeling of human HCC in immune-compromised NOD-Rag1null IL2rgnull (NRG) mice using Hep3B cells results in reduced tumor weight upon ACLY knockdown.